THE EFFECTS OF THE LEADERSHIP AND THE HUMAN RESOURCE CAPABILITY UPON THE SERVICE EFFECTIVENESS OF THE CERTICATION OF LAND OWNERSHIP AT THE AGRARIAN AFFAIRS OFFICE OF TANGERANG - Dudung Hadiwijaya (The Management Journal of Binaniaga, 2018)
The purpose of the research is to examine the influence of the leadership and HR ability upon the service effectiveness of the land property rights at the Agrarian Office of Tangerang City. The result of the research has indicated that the leadership and HR ability are simultaneously having a significant effect upon the service effectiveness. The result also has indicated that the leadership is having more dominant and significant effect rather than HR ability towards the service effectiveness of the land property rights at the Agrarian Office of Tangerang City.Keywords: the leadership, HR ability, service effectiveness